Intramuscular lipomatosis of tongue. Issue 919 (1st May 2002) - Thomas, S; Varghese, B T; Sebastian, P; Koshy, C M; Mathews, A; Abraham, E K
Abstract : A rare case of intramuscular lipomatosis of the tongue with intramuscular invasion in a 42 year old man is presented. The literature is reviewed and the clinical features, pathology, and treatment are discussed briefly.